Peran Program Adiwiyata dalam Pembentukan Karakter Peduli Lingkungan untuk Mendukung Mitigasi Bencana di Sekolah Menengah Pertama Kota Semarang - Mulianingsih, Ferani; Kintoko, Kintoko; Permana, Septian Aji; Astuti, Andarweni; Suprapto, Yuni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to examine the integration of the Adiwiyata Program in the formation of an environmentally caring character as a disaster mitigation effort based on educational units. The research was conducted with a participatory approach at SMP Negeri 4 and SMP Negeri 29 Semarang through three main stages: planning, implementation, and evaluation. The results indicate an increase in student awareness and involvement in sustainable environmental management, active participation in green school programs, and a real role in building a culture of disaster preparedness. Character strengthening is carried out through habituation, exemplification, and integration of environmental materials into the curriculum. This strategy has proven effective in enhancing students' adaptability to disaster threats related to environmental damage, such as floods and landslides. These findings emphasize the importance of collaboration between character education and the implementation of the Adiwiyata Program to shape a school ecosystem